SUPPORTING FAMILIES IN CORRECTING DYSLALIA IN CHILDREN - Siedlaczek-Szwed, Aleksandra; Jałowiecka-Frania, Agata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The text deals with issues related to the effective support of speech and language therapy for children with dyslalia. The effectiveness of speech and language stimulation is determined by a wide range of determinants. Individual predispositions, influences of educational environments, personality, professionalism, the scope of speech and language therapists’ knowledge and abilities as well as a variety of methods used by them play an essential role. Dyslalia, which is one of the most frequent speech disorders, has a negative and significant impact on children’s psychosocial functioning. Children’s attitudes toward peers with speech articulation disorders not only seem to affect intellectual, cognitive and motivational processes, including perception, attention, memory, thinking, but also transform social behaviours. Therefore, the profound significance of the family’s influence on the effectiveness of speech and language therapy for children with dyslalia has been emphasised. It is assumed that educational activities require planned, intentional and regular collaboration with various environments in order to achieve desired goals and shape comprehensive individual development.